Iridium‐Catalyzed Dehydrogenation in a Continuous Flow Reactor for Practical On‐Board Hydrogen Generation From Liquid Organic Hydrogen Carriers. Issue 8 (25th March 2022) - Polukeev, Alexey V.; Wallenberg, Reine; Uhlig, Jens; Hulteberg, Christian P.; Wendt, Ola F.
Abstract: To enable the large‐scale use of hydrogen fuel cells for mobility applications, convenient methods for on‐board hydrogen storage and release are required. A promising approach is liquid organic hydrogen carriers (LOHCs), since these are safe, available on a large scale, and compatible with existing refueling infrastructure. Usually, LOHC dehydrogenation is carried out in batch‐type reactors by transition metals and their complexes and suffers from slow H2 release kinetics and/or inability to reach high energy density by weight, owing to low conversion or the need to dilute the reaction mixture. In this study, a continuous flow reactor is used in combination with a heterogenized iridium pincer complex, which enables a tremendous increase in LOHC dehydrogenation rates. Thus, dehydrogenation of isopropanol is performed in a regime that, in terms of gravimetric energy density, hydrogen generation rate, and precious metal content, is potentially compatible with applications in a fuel‐cell powered car. Abstract : Get on board : Heterogenized iridium pincer complexes are used in a continuous flow reactor to enable dehydrogenation of isopropanol as a liquid organic hydrogen carrier (LOHC) at high temperatures, well above the boiling point, providing a tremendous boost of activity in hydrogen production compared to related homogenous systems.